Relationship between core stability, dynamic balance and jumping performance in soccer players - Tarik Ozmen (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to investigate relationship between core stability, dynamic balance and jumping performance in soccer players. Seventeen male soccer players (mean ± SD: age, 21.06 ± 1.71 years) participated as volunteer in this study. Dynamic balance of the participants were evaluated at directions of anterior (A), posteromedial (PM) and posterolateral (PL) with Star Excursion Balance Test (SEBT). The core stability was evaluated with trunk flexion, side bridge, and trunk extension tests. For jumping performance, squat jump height was measured using a contact mat. There was a negative correlation (r = -0.705) between trunk flexion test and squat jump height (p lt; 0.002). No significant correlation were identified between trunk flexion, side bridge, trunk extension tests and squat jump height (p gt; 0.05). There was no significant correlation between trunk flexion, side bridge, trunk extension tests and SEBT values (p gt; 0.05). The results of this study suggest that trunk flexion is associated with squat jump height in soccer players, but not side bridge and trunk extension tests. The core stability does not contribute significantly on dynamic balance.